Valorization of aromatic and Medicinal Plants of Ranomafana, District Ifanadiana, Region Vatovavy Fitovinany: Case of Vepris ampody and Vepris sp - Ratalata R. B.; Razafindrazanakolona D.; Robijaona Rahelivololoniaina B.; Ratalata R. F.; Koto-Te-Nyiwa Ngbolua (Britain International of Exact Sciences (BIoEx) Journal, 2023)
For the conservation of the biodiversity of Ranomafana, the valorization of the aromatic and medicinal plants of Ranomafana is an alternative. Two plants of the RUTACEAE family were chosen Vepris ampody and Vepris sp. For this a multidisciplinary approach was adopted: an ethnobotanical survey for the traditional use, ecology of the plant in order to identify environmental conditions favorable to the development of the species, phytochemical screening and identification of the essential oils of the leaves, isolation of mycoendophytes and identification of the fatty acids resulting from the extracts of fermentation. Vepris ampody is used in traditional medicine, and the decoction of leaves and bark is used in case of fever, malaria, fatigue, and muscle pain. The leaves are rich in alkaloids and the essential oils in sabinene. Four strains have been isolated. After fermentation, these four strains produce fatty acids, mostly unsaturated. Vepri ssp. has no medicinal use, it is used to ward off a spell. The leaves are rich in alkaloids. The essential oil is rich in linalool. The perspectives of the study concern the popularization of culture and the identification of alkaloids.